Tourism demand elasticities by income and prices of international market regions: Evidence using Vietnam's data - Nguyen Quang Hai (Economies, 2022)
This study aims to determine tourism demand elasticities by income and prices of regions, as well as total international markets. It is deployed to a total of 10 major source markets and two separate regions, from Asia and intercontinental to Vietnam. The results of data analysis for the period 1995–2019 and using a nonlinear panel ARDL approach show that tourism demand from major Asian markets to Vietnam is strongly income elastic, but tourism demand from major intercontinental markets to Vietnam is relatively price inelastic. Tourism demand in intercontinental markets is less elastic to price, but in Asian markets it is quite price sensitive, especially own price elasticities. In addition, different effects of income and prices are found in most of the major markets. Study results have provided useful insights into different types of tourism goods and price sensitivity between market regions, as well as the degree of substitute destinations.
Keywords: 330; income and prices; international market regions; tourism demand elasticities